RUSTY BOLTS AND BROKEN VALVES: A STUDY ON THE PLANT TECHNOLOGY, SIZE, AND ORGANIZATIONAL STRUCTURE OF PLANT TURNAROUND MAINTENANCE IN MALAYSIAN PROCESS-BASED INDUSTRIES - Ghazali, Zulkipli; Halib, Mohammed; Md Nordin, Shahrina; Che Ghazali, Maznah (Intellectbase International Consortium, 2009)
Plant turnaround maintenance, a crucial asset management in technology intensive industries is carried out to revitalize, maintain, and improve the plant facilities for optimal and efficient performance. This paper discusses the relationship of plant technology, size, and organizational structure in plant turnaround maintenance of 58 companies in six process-based industries in Malaysia. Seven hypotheses were tested using nonparametric statistical analysis. The test results support the hypotheses and provide evidence that plant technology influences the organization of turnaround maintenance. Results of the analysis also showed differences in the size of the turnaround maintenance that point towards variation in the six types of plant technology employed by the companies covered in the study.